2020
DOI: 10.1038/s41598-020-61900-8
|View full text |Cite
|
Sign up to set email alerts
|

Milk yield, milk composition, and milk metabolomics of dairy goats intramammary-challenged with lipopolysaccharide under heat stress conditions

Abstract: Heat stress and mastitis are major economic issues in dairy production. the objective was to test whether goat's mammary gland immune response to E. coli lipopolysaccharide (LpS) could be conditioned by heat stress (HS). changes in milk composition and milk metabolomics were evaluated after the administration of LpS in mammary glands of dairy goats under thermal-neutral (tn; n = 4; 15 to 20 °C; 40 to 45% humidity) or HS (n = 4; 35 °C day, 28 °C night; 40% humidity) conditions. Milk metabolomics were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 43 publications
3
10
0
Order By: Relevance
“…Yields of milk fat, protein, and lactose were also depressed ( p < 0.05) by HS ( Table 2 ). Although mammary immunity is hindered by HS [ 30 ], heat load in the current study had no significant effect on milk somatic cell count, which is in accordance with the results obtained in dairy goats [ 6 , 7 ] and sheep [ 31 ].…”
Section: Resultssupporting
confidence: 91%
“…Yields of milk fat, protein, and lactose were also depressed ( p < 0.05) by HS ( Table 2 ). Although mammary immunity is hindered by HS [ 30 ], heat load in the current study had no significant effect on milk somatic cell count, which is in accordance with the results obtained in dairy goats [ 6 , 7 ] and sheep [ 31 ].…”
Section: Resultssupporting
confidence: 91%
“…Studies have shown 35% decline for mid-lactation [69] and 14% for early lactation cows [94]. Besides milk yield and composition HS increased the somatic cell count of the milk [97] through initiation of immune response in the mammary tissue [98]. HS tend to activate immune system, which is energy intensive phenomena; therefore, the glucose consumption in dairy cow is increased [99].…”
Section: Effects On Milk Productionmentioning
confidence: 99%
“…When formulating diets, milk producers should keep in mind these metabolic changes during the scarcity of pastures during the dry season, leading to seasonal weight loss. Recently, Salama and coworkers [ 48 ] observed changes in goat milk chemical profiles when animals were subjected to heat stress or treated with E. coli lipopolysaccharide (LPS). LPS febrile response was masked in heat-stressed goats.…”
Section: Selected Instrumental Techniques and Their Applicationsmentioning
confidence: 99%